IMPERFECT PEACE AND THE ZAWIYA IN THE EASTERN RIF: THE TRANSFORMATION OF SUFI BROTHERHOODS IN POST-INDEPENDENCE MOROCCO - Ouragh Ouragh, Aziz (Religi: Jurnal Studi Agama-agama, 2025)
This article presents a theoretical approach rooted in Peace Research to examine the religious landscape of the eastern Rif following Morocco's independence. The period of independence positioned religious entities at a critical juncture in their long history, representing a particularly unstable time for the Sufi brotherhoods associated with these zawiya. The social spaces created by the zawiya have been influenced by new sociocultural dynamics, leading to their transformation and adaptation in response to contemporary demands. This study aims to guide the reader toward understanding peace as an ongoing journey that coexists with conflict, highlighting the peaceful elements that emerge within these Sufi entities. Insights derived from research on peace, particularly the theory of Imperfect Peace, illuminate the dynamism of the zawiya, their roles as agents of social harmony, and the space-time transformations they undergo in the pursuit of continuous and transformative peace. This exploration focuses on one of the most deeply rooted entities in the eastern Rif.   Keyword: Imperfect Peace, peacebuilding, Zawiya, Rif, independence.   Artikel ini meneliti pendekatan teoretis yang berakar pada penelitian perdamaian untuk mengkaji lanskap keagamaan di Rif timur pasca kemerdekaan Maroko. Periode kemerdekaan di sana menempatkan entitas-entitas keagamaan pada titik kritis dalam sejarah panjang mereka, yang mewakili masa yang sangat tidak stabil bagi persaudaraan Sufi yang terkait dengan Zawiya ini. Ruang sosial yang diciptakan Zawiya dipengaruhi oleh dinamika sosio-kultural baru yang mengarah pada transformasi dan adaptasi menghadapi tuntutan-tuntutan kontemporer pada masanya. Studi ini bertujuan membahas perdamaian sebagai perjalanan berkelanjutan yang hidup berdampingan dengan konflik, dengan menyoroti elemen-elemen damai yang muncul dalam entitas-entitas Sufi ini. Wawasan yang diperoleh dari penelitian tentang perdamaian, khususnya teori Perdamaian yang Tidak Sempurna, menyoroti dinamisme Zawiya, peran mereka sebagai agen harmoni sosial, dan transformasi ruang-waktu yang mereka alami dalam mengejar perdamaian yang berkelanjutan dan transformatif. Eksplorasi ini berfokus pada salah satu entitas yang paling mengakar di Rif Timu, Maroko.   Kata kunci: Perdamaian yang Tidak Sempurna, pembangunan perdamaian, Zawiya, Rif, kemerdekaan.